2018
DOI: 10.26438/ijsrpas/v6i6.8087
|View full text |Cite
|
Sign up to set email alerts
|

Structural, Optical and Electrical conductivity Studies of Mn2+ Ions Doped PVAMAAEA Polymer Blend Films

Abstract: Pure and different concentrations of Mn 2+ (1.0, 2.0, 3.0, 4.0 and 5.0 mol%) doped PVA/MAA:EA polymer blend films were prepared by solution casting method. The structural analysis of the prepared samples by X-ray Diffraction reveals broadening of diffraction peak which implies a lower degree of crystallinity with higher Mn 2+ concentration. UV-Vis spectral analysis shows a significant red shift in the optical band gap with increase in Mn 2+ concentration. FTIR spectrum exhibits bands characteristic of stretch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…It observed that pure PVA has a smooth network structure. Ag nanoparticles were homogeneously distributed within the PVA matrix film and nanoparticles displayed nearly spherical shapes [19][20]. The presence of Ag was confirmed by the elemental analysis Energy Dispersive X-ray Spectroscopy (EDX), presented in Figure .11.…”
Section: Sem and Edx Analysismentioning
confidence: 76%
See 1 more Smart Citation
“…It observed that pure PVA has a smooth network structure. Ag nanoparticles were homogeneously distributed within the PVA matrix film and nanoparticles displayed nearly spherical shapes [19][20]. The presence of Ag was confirmed by the elemental analysis Energy Dispersive X-ray Spectroscopy (EDX), presented in Figure .11.…”
Section: Sem and Edx Analysismentioning
confidence: 76%
“…Figure . 9, represents the effect of gamma irradiation, the intensity of bands has been observed to decrease further along with the disappearance of bands in the wave number of 2852 and 1654 cm -1 , with increasing gamma dose. This indicates that gamma irradiation subsequently causes the structural rearrangements in PVA chains on the embedding of Ag nanoparticles [17][18].…”
Section: Resultsmentioning
confidence: 98%
“…For (PVA‐PVP)/Er 3+ films, the relationship between the absorption coefficient and photon energy hv was displayed in Figure 5a,b. As the Er 3+ wt% rose, it was observed that the absorption edge values for the (PVA‐PVP)/Er 3+ films decreased noticeably, suggesting the creation of certain localized states in the bandgap and the growth of compositional disorder 49–51 . The Urbach rule may explain the exponential dependency of the absorption coefficient at the band edge on photon energy 52,53 …”
Section: Resultsmentioning
confidence: 99%